If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 47 = 82 Reorder the terms: 47 + X = 82 Solving 47 + X = 82 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-47' to each side of the equation. 47 + -47 + X = 82 + -47 Combine like terms: 47 + -47 = 0 0 + X = 82 + -47 X = 82 + -47 Combine like terms: 82 + -47 = 35 X = 35 Simplifying X = 35
| 3(2x-4+x)=14 | | -3+9=-4r+5 | | .4(z-0.8)=1.6(z-.2) | | y=(-x^2)+6x-12 | | 2ax-4b=-6c | | (2x-5y+6)-(-4x-3y+7)= | | 2(2x-4)+8(8x+1)=-272 | | A+14=38 | | 7x-3x+1=5-4x-8 | | -0.5m-3=9 | | X+15=43 | | -8(x+1)-(-9x+9)=7 | | 3/8(n+4/5)=-3/8(n-5) | | M-51=23 | | 16x-19X= | | -3x+5=8-4(x-3) | | P-56=12 | | x*2x=48 | | 7X+9Y=42 | | 3x-3y=11 | | -7y-5y=4/5 | | 12x+2y= | | -2m-8m=5/7 | | 7m+3-4m= | | 2x(y+1)-2y(x+1)=0 | | 7x+8=9x+5 | | 1/4-3/5=z/20 | | 1/2-3/5=x/10 | | 20=-2(m+3)+m | | 4+v-5=16 | | 3+d-4=12 | | 145=5x-5(-1x-5) |